Pemberian Terapi Akupresur sebagai Upaya Peningkatan Kualitas Tidur dan Kadar Estrogen pada Wanita Menopause - Nainggolan, Wiwiek; Mardiyono, Mardiyono; Suwondo, Ari (LPPM Hang Tuah Pekanbaru, 2024)
The decrease in the hormone estrogen during menopause causes the quality of sleep to decrease. Sleep quality affects physical and psychological health which can reduce the quality of life of menopause. This study aims to prove that acupressure therapy can improve sleep quality and estrogen hormone levels in postmenopausal women. The design of this study is a Quasi experiment, which is by using existing groups. The number of samples was 40 respondents, selected using the Consecutive Sampling technique. The intervention group was given acupressure therapy on HT 7, PC 6, and GV 20 points 6 times for 2 weeks. Sleep quality was measured by the Pittsburgh Sleep Quality Index (PSQI) questionnaire and estrogen levels were measured by the ELISA method. Data analysis using Paired Sample Test and independent T-Test. Data analysis showed a change in the mean score of sleep quality and estrogen levels in the intervention group after being given acupressure therapy intervention (p = 0.000) (effect size = 0.90). Hasil dari penelitian ini terdapat perbedaan rerata skor kualitas tidur dan skor kadar estrogen antara kelompok intervensi dan kontrol (p = 0,000) (effect size=1.17). The conclusion of this study is acupressure therapy at points HT 7, PC 6, and GV 20 can improve sleep quality and estrogen hormone in menopausal women. This study implies that acupressure therapy interventions can be applied as part of obstetric care in menopausal women.